PENDIDIKAN BERKEUNGGULAN INSAN - Gunawan Gunawan (Jurnal Cakrawala Pendidikan, 2007)
In existentialism, the existence of one thing is always in the companyofone or more other things.Thus, to give a correct idea or to avoid misunderstandingsof theuseof the predicate unggul as in terms like bibit unggul, sekolahunggulan, produk unggulan pendidikan, and others, it is morallyimperative for the usersof such terms to provide the terms with theircontexts to determine whether unggul means 'prime', 'superior','competitive', or any other. Instancesof such contexts can be ofappearance or performance, of a long or short term, of currentobjectives or future goals, of individuals or the community, ofindividual or social needs, of national or international needs, ofinclusive or exclusive purposes, and others. Even now, the writer isstillof the belief that the usage of those aforementioned terms in thefieldof education in Indonesia is still more as jargon rather thanbasic concepts. Indeed very rarely or even never does the public,particularly those who are very much concerned with thedevelopmentof education in Indonesia, to get a thoroughexplanationof those terms mentioned.This article tries to build a kindof "second opinion" as abalance to the existenceofthat jargon menti